Unanticipated money - Thomas F. Cooley; Gary D. Hansen (Institute for Advanced Studies (IHS), 1997)
The role of unanticipated changes in money growth for aggregate fluctuations is reexamined using the methods of quantitative equilibrium business cycle theory. A stochastic growth model with money is constructed that has the feature, following Lucas (1972, 1975), that production and trade take place in spatially separated markets (islands). Individuals must infer changes in the aggregate price level from observing local relative prices. This causes individuals to react to changes in the average price level, due to unanticipated changes in the aggregate money supply, as though they were changes in market specific relative prices. We show that this mechanism can lead to quantitatively large fluctuations in real economic activity. The statistical properties of these fluctuations, however, are quite different from the properties of fluctuations observed in the U.S. economy.
Keywords: E32; E52; 330; business cycles; monetary policy; aggregate fluctuations; real business cycles; Real Business Cycle; Geldmenge; Theorie